Yemeni Narrative and Society: Socio-political Issues in Dammaj’s The Hostage - Altwaiji, Mubarak; Telha, Mona (Journal of History Culture and Art Research, 2020)
Narrative writing is relatively a new phenomenon in Yemeni literary discourse and a sequel to the maturity of the common folk forms. The present study investigates both the rise of Yemeni novel and the representation of the major social and economic issues in early Yemeni novel between the 1970s-1980s. Since the 1970s, the novel genre has become one of the most relevant phenomena in Yemeni literary canon. Yemeni writers of this era were aware of the importance of introducing contemporary issues to the reader. In addition to this task, the novel has enriched the Yemeni cultural field and remained dynamic in national identity formation. This study has a special reference to Zayd Dammaj’s The Hostage (1984) for it is the first Yemeni novel that has unflinching determination and frankness in representing injustices and miseries in the society. Though The Hostage is also a tender critique of influential families that were part of the oppressive regime, it succeeds in helping the nation compromise with the past. The conclusion of the study suggests that while criticizing certain families for the misery of the whole nation may challenge co-existence, this discourse is seen as a subtle manifestation of negotiating differences. Further, the conclusion of this study finds that investigating history and major issues in Yemeni novel will guide readers and critics to a much-needed area of study on the factors which led to the rise of the Yemeni novel.